3-D dosimetry for Gamma Knife by using the normoxic gel - (:unkn) unknown (My University, 2008)
Unlike the conventional radiotherapy, the dosimetry in Gamma Knife is complicated due to geometry of the γ-beams. A normoxic polymer gel phantom is prepared in a spherical glass balloon of 16 cm diameter. The phantom that is irradiated is scanned in the MR unit, as the degree of polymerization affects the relaxation time constants of the gel. Linearity is observed between the delivered dose and the reciprocal of the gel T2 relaxation time constant. For dose calibration, 100 ml gel containing vials are irradiated at predefined doses. Dose distributions are the results of a single shot of irradiation, obtained by collimating all 201 Cobalt sources to a known target in the phantom. Stereotactic frames and fiducial markers are attached to the phantom for MR scanning. The dose distribution predicted by the Gamma Knife planning system is compared with that of the gel Dosimetry. The results with the gel phantom are in good agreement with the GammaPlan predicted values; the isodose diameters measured by the gel dosimetry and the GammaPlan differed by 5% at most. The normoxic gel phantom can be used clinically in 3-D dose assessment of the quality control measurements of the Gamma Knife.
Keywords: Dose measurement; Gamma Knife; Gel Dosimetry; Normoxic gel